Cortisol-related metabolic alterations assessed by mass spectrometry assay in patients with Cushing's syndrome. Issue 2 (August 2017) - Di Dalmazi, Guido; Quinkler, Marcus; Deutschbein, Timo; Prehn, Cornelia; Rayes, Nada; Kroiss, Matthias; Berr, Christina M; Stalla, Günter; Fassnacht, Martin; Adamski, Jerzy; Reincke, Martin; Beuschlein, Felix
Abstract : Objective: Endogenous hypercortisolism is a chronic condition associated with severe metabolic disturbances and cardiovascular sequela. The aim of this study was to characterize metabolic alterations in patients with different degrees of hypercortisolism by mass-spectrometry-based targeted plasma metabolomic profiling and correlate the metabolomic profile with clinical and hormonal data. Design: Cross-sectional study. Methods: Subjects ( n = 149) were classified according to clinical and hormonal characteristics: Cushing's syndrome ( n = 46), adrenocortical adenomas with autonomous cortisol secretion ( n = 31) or without hypercortisolism ( n = 27). Subjects with suspicion of hypercortisolism, but normal hormonal/imaging testing, served as controls ( n = 42). Clinical and hormonal data were retrieved for all patients and targeted metabolomic profiling was performed. Results: Patients with hypercortisolism showed lower levels of short-/medium-chain acylcarnitines and branched-chain and aromatic amino acids, but higher polyamines levels, in comparison to controls. These alterations were confirmed after excluding diabetic patients. Regression models showed significant correlation between cortisol after dexamethasone suppression test (DST) and 31 metabolites, independently of confounding/contributing factors. Among those, histidine and spermidine were also significantly associated with catabolic signs and symptoms of hypercortisolism. According to an discriminant analysis, the panel of metabolites was able to correctly classify subjects into the main diagnostic categories and to distinguish between subjects with/without altered post-DST cortisol and with/without diabetes in >80% of the cases. Conclusions: Metabolomic profiling revealed alterations of intermediate metabolism independently associated with the severity of hypercortisolism, consistent with disturbed protein synthesis/catabolism and incomplete β-oxidation, providing evidence for the occurrence of metabolic inflexibility in hypercortisolism.